THE CONFLICT BETWEEN NIGERIA AND CAMEROUN OVER LAND AND SEA BORDERS AND TERRITORIES: THE POLITICAL CONTEXT’AND THE .CONTENDING· PRINCIPLES - Asobie, H.A (University of Nigeria Journal of Political Economy, 2022)
This article is the product of a study of the international conflict between two neighbouring, under-developed African states, Nigeria and Cameroun. It is an analysis of the principles and norms thrown up by a conflict situation, and of the domestic political and economic contexts of international conflicts, placed in a historical perspective.